Endemic Diseases and Development: An overview - (:unkn) unknown (My University, 2010)
Evidence abounds to support the view that while health, measured by life expectancy, had improved, and converged in the world, the income or economic prosperity did not. Recent literature tried to show that poor health and endemic diseases in Africa may constitute a barrier to growth. However, the connections between health and economic development are controversial. The papers presented in this volume deal with this issue and discuss the different channels by which diseases affect the economy and how adequate policy may improve health. The first paper by T. Paul Schultz on health human capital and economic development analyses the interrelations between health and economic development raising the difficulty of estimating those connections due to some methodological constraints. He also shows the importance of distinguishing between the technology of ‘health production functions' and the relationship between an individual's stock of health and her or his economic productivity, duration of life and returns to health human capital. He underlines that in low-income countries and specifically in Africa, improvements in nutrition and control of endemic diseases concentrated in childhood were relatively cheap and have contributed to a convergence of lifespan. And the prior reduction in childhood illnesses may itself contribute to improved adult health outcomes later in the life, such as to increase their potential economic productivity as adults. The second paper by D. Weil on endemic diseases and African economic growth argues about the need for investing more in health in Africa, as the actual income gain from better health and endemic disease elimination is large. Considering that the burden of diseases is not only a public health matter but also an economic matter, the author focuses on the effect of diseases on economic growth. He shows that its effects act through numerous channels at different time horizons. A simulation model that may describe thes
Keywords: African Research